(3JYde (BAdobe Illustrator cs3s ((3GdbGgQIs Pc Lab, 2007)
(3aj gPg GdeLehYI GdJYdjejI Sha fJYQa Ydj HQfGeL (BAdobe Illustrator CS3 (3hGdPj jYJHQ ef Cbhj HQGeL GdQSe hYed GdJUejeGJs
(3eQab cJGH eY gPg GdCSWhGfGJs
1 2 3 12
Keywords: (3GdMGSHGJ GdEdcJQhfjIs -- (3HQGeLs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs